2015
DOI: 10.1167/tvst.4.5.7
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Signal Intensity on Measurement of Ganglion Cell Complex and Retinal Nerve Fiber Layer Scans in Fourier-Domain Optical Coherence Tomography

Abstract: Citation: Zhang X, Iverson SM, Tan O, Huang D. Effect of signal intensity on measurement of ganglion cell complex and retinal nerve fiber layer scans in Fourier-Domain optical coherence tomography. Trans Vis Sci Tech. 2015;4(5):7, doi:10.1167/ tvst.4.5.7 Purpose: We determined the effect of Fourier-domain optical coherence tomography (OCT) signal strength index (SSI) and cropping on retinal nerve fiber layer (RNFL) and macular ganglion cell complex (GCC) scan repeatability and measurement thickness.Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 30 publications
5
43
0
Order By: Relevance
“…The NFL regression further took into account the known effect of OCT signal strength (measured by SSI) on thickness measurement. 42 Taking out the aging adjustment increased the rate of detecting glaucoma progression by GCC and NFL thinning at the cost of decreased specificity. This increase in detection rate was statistically significant for both GCC and NFL in PG and GS/PPG group (P<0.001, P<0.001 for GCC, P=0.014, P < 0.001 for NFL).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The NFL regression further took into account the known effect of OCT signal strength (measured by SSI) on thickness measurement. 42 Taking out the aging adjustment increased the rate of detecting glaucoma progression by GCC and NFL thinning at the cost of decreased specificity. This increase in detection rate was statistically significant for both GCC and NFL in PG and GS/PPG group (P<0.001, P<0.001 for GCC, P=0.014, P < 0.001 for NFL).…”
Section: Resultsmentioning
confidence: 99%
“…The default analysis in this paper averaged measurements from 3 sets of OCT scans at each visit, accounted for the rate of normal age-related thinning in NFL and GCC, 43 and compensated for the effect of OCT signal strength variation on NFL measurements. 42 This differs from the standard clinical practice, where one OCT scan is made at each visit, and no compensation for signal strength or aging changes is made in the linear regression analysis software on the commercial RTVue OCT system software. Our analysis found that accounting for the change over time in NFL and GCC due to normal aging had significant effects on detecting progression; therefore it is desirable to adjust for aging effect when using the trend of NFL and GCC to define progression.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…So far, no minimum image quality parameters for OCT-A CC measurements have been defined. Zhang et al [35] discussed the influence of SSI on image quality in OCT measurements using a Zeiss OCT instrument and concluded that a minimum of signal strength has to be reached to provide constant and reliable image quality. Cutoffs were defined at ≥ 37 SSI for retinal nerve fiber layer and ≥ 44 for ganglion cell complex measurements.…”
Section: Signal Strengthmentioning
confidence: 99%